2010
DOI: 10.1167/iovs.09-3996
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of UV-Induced Damage to the Anterior Segment Using Class I UV-Absorbing Hydrogel Contact Lenses

Abstract: The authors show that senofilcon A class I UV-blocking contact lenses are capable of protecting the cornea, aqueous humor, and crystalline lens of rabbits from UV-induced pathologic changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 63 publications
1
42
0
Order By: Relevance
“…UV light has been shown to cause apoptosis in lens cells and in whole lenses (21,22,(27)(28)(29) and because UV light exposure is associated with cataract formation (18 -20), we sought to determine the effect of UVA light on the subunits of the integrin ␣V␤5 receptor and on the process of lens cell phagocytosis of apoptotic debris. To test this, human SRA 01/04 lens epithelial cells were exposed to UVA light using a UVA LED array.…”
Section: Uva Treatment Of Lens Epithelial Cells Results In Loss Of Bomentioning
confidence: 99%
See 3 more Smart Citations
“…UV light has been shown to cause apoptosis in lens cells and in whole lenses (21,22,(27)(28)(29) and because UV light exposure is associated with cataract formation (18 -20), we sought to determine the effect of UVA light on the subunits of the integrin ␣V␤5 receptor and on the process of lens cell phagocytosis of apoptotic debris. To test this, human SRA 01/04 lens epithelial cells were exposed to UVA light using a UVA LED array.…”
Section: Uva Treatment Of Lens Epithelial Cells Results In Loss Of Bomentioning
confidence: 99%
“…A major insult to the lens epithelium is UV light exposure (21)(22)(23)(24). The human cornea absorbs all incident light below 300 nm wavelength and ϳ92% of UVB between 300 and 315 nm (24,83,84).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal models have shown that UV-blocking contact lenses can directly reduce UV-induced oxidative damage to the cornea, aqueous, lens (Chandler et al, 2010) and retina (Ibrahim et al, 2012). A number of organizations (e.g., the American Optometric Association) and comprehensive reviews (Chandler, 2011;Walsh and Bergmanson, 2011) have endorsed the use of UV-blocking contact lenses covering the limbus as greatly reducing the potentially toxic effect of light-induced oxidative damage to the eye.…”
Section: Uv and Short-wave Light Absorption By Spectacle And Contact mentioning
confidence: 99%